2004
DOI: 10.1128/jb.186.11.3609-3620.2004
|View full text |Cite
|
Sign up to set email alerts
|

TheSinorhizobium meliloti furGene Regulates, with Dependence on Mn(II), Transcription of thesitABCDOperon, Encoding a Metal-Type Transporter

Abstract: Sinorhizobium meliloti is an alpha-proteobacterium able to induce nitrogen-fixing nodules on roots of specific legumes. In order to propagate in the soil and for successful symbiotic interaction the bacterium needs to sequester metals like iron and manganese from its environment. The metal uptake has to be in turn tightly regulated to avoid toxic effects. In this report we describe the characterization of a chromosomal region of S. meliloti encoding the sitABCD operon and the putative regulatory fur gene. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 71 publications
5
89
0
Order By: Relevance
“…These characterizations were consistent with the decrease in healthy pink nodules observed on sitA::mTn5 mutant-inoculated plants. While we were characterizing the sitA::mTn5 mutant, a report describing a sitA deletion was published (10). In agreement with our observations, that report showed that acetylene reduction was decreased for alfalfa inoculated with the sitA deletion strain, but the physiology of the symbiotic defect was not further characterized.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…These characterizations were consistent with the decrease in healthy pink nodules observed on sitA::mTn5 mutant-inoculated plants. While we were characterizing the sitA::mTn5 mutant, a report describing a sitA deletion was published (10). In agreement with our observations, that report showed that acetylene reduction was decreased for alfalfa inoculated with the sitA deletion strain, but the physiology of the symbiotic defect was not further characterized.…”
Section: Resultssupporting
confidence: 80%
“…Our findings are consistent with studies of SitABCD homologs in S. enterica serovar Typhimurium, which showed that SitABCD can transport both Fe 2ϩ and Mn 2ϩ but that transport of Mn 2ϩ is favored 100 times over that of Fe 2ϩ (30). Previous work suggested that Mn 2ϩ alone could not rescue the growth defect of a sitA deletion strain (10). The authors of that work graciously sent us their sitA deletion strain for comparison with our sitA::mTn5 strain.…”
Section: Discussionsupporting
confidence: 80%
“…Association of Mn 2+ with Mur confers DNA binding activity on the protein, resulting in occupancy of the mntH promoter by Mur and transcriptional repression (13,15). The responsiveness of the Fur-like regulator Mur to Mn 2+ in B. japonicum and other α-Proteobacteria rather than to Fe 2+ (13,(15)(16)(17)(18)(19) may reflect an adaptation by this group to a more manganese-dependent metabolism. In support of this, an mntH mutant of B. japonicum has a severe growth phenotype (13), whereas other bacterial mntH mutants do not unless they are exposed to oxidative stress (20).…”
mentioning
confidence: 99%
“…Consistent with this, Rhizobium has a gene whose product resembles a 'classical' Fur, but mutations in the fur-like gene do not affect Feresponsive regulation of the fhu, vbs, rpoI, hmu and tonB genes alluded to above (Wexler et al, 2003). Indeed, this Fur-like protein is actually a manganese-sensing regulator, termed 'Mur', which represses the operon that specifies a Mn 2+ ABC transporter, SitABCD, in Mn 2+ -replete cells (Diaz-Mireles et al, 2004;Chao et al, 2004). …”
Section: Introductionmentioning
confidence: 99%